CHEMICAL AND SENSORY MEAT CHARACTERISTICS OF NELLORE CATTLE (Bos indicus) FINISHED WITH DIFFERENT LEVELS OF BACKFAT THICKNESS IN THE LONGISSIMUS THORACIS MUSCLE - Malheiros, Jessica Moraes [UNESP]; Baldassini, Welder Angelo [UNESP]; Domingos Dias, Victor Augusto [UNESP]; Vasconcelos Silva, Josineudson Augusto I. I. [UNESP]; Curi, Rogerio Abdalah [UNESP]; Loyola Chardulo, Luis Artur [UNESP] (Inst Zootecnia, 2015)
The objective of this study was to evaluate the effect of backfat thickness (BFT) on the meat quality of feedlot-finished Nellore bulls (Bos indicus). Seventy-two animals were feedlot finished for about 100 days. For this study, 24 animals were sampled according to BFT in the longissimus thoracis muscle after slaughter: 12 animals with BFT up to 3.0 mm (class BFT-3) and 12 animals with BFT >6.0 mm (class BFT-6). Chemical (myofibrillar fragmentation index, intramuscular fat content, and unsaturated and saturated fatty acids) and physical (cold carcass weight, rib eye area, and marbling score) characteristics of the meat were evaluated. Additionally, shear force and sensory characteristics (aroma, flavor, tenderness, chewiness, and juiciness) were analyzed. Marbling score and intramuscular fat content were considered low for the two BFT classes. The mean values of the characteristics studied did not differ (P>0.05) between BFT classes, except for fatty acids, with the observation of higher unsaturated fatty acid levels in the BFT-6 class. There was no difference (P>0.05) in sensory characteristics between BFT classes. The most consistent relationship was observed between the myofibrillar fragmentation index and tenderness, measured as shear force, in animals with greater BFT (BFT-6 class) compared to animals with lower BFT (BFT-3 class), suggesting possible tenderness problems in animals with a leaner carcass. The observation of a higher concentration of unsaturated fatty acids in animals with greater BFT suggests an increase in the sensory perception of meat, especially flavor.
Keywords: sensory analysis; fat composition; muscle growth; tenderness